Alternative Technologies for Controlling CO2 Emissions and Energy Costs Minimization in Manufacturing Processes - Ilham Kissani; Asmae el Mokrini (International Journal of Supply Chain Management, 2013)
Provided that energy consumption goes together with CO2 emissions and high production costs, multinational companies seek perpetually to implement the best practices in an effort to satisfy customers not in terms of fair prices, quality and quantity delivered but also in terms of delivering products that respect environmental regulations. It seems that it is no longer optional for companies to opt for environmental practices, while having two major reasons to remain cost efficient and customer seductive: their production processes will no more tolerate waste in energy and their customers are consciously more than ever seeking eco-friendly products. In this paper, we conduct a cost analysis based on a comparison traditional with eco-friendly technologies in manufacturing detergent products based on different sources of energy.